Different pre‐scanning instructions induce distinct psychological and resting brain states during functional magnetic resonance imaging. (20th December 2017) - Kawagoe, Toshikazu; Onoda, Keiichi; Yamaguchi, Shuhei
Abstract: Resting‐state functional magnetic resonance imaging (rs‐fMRI) is widely used to investigate functional brain network connectivity during rest or when the subject is not performing an explicit task. In the standard procedure, subjects are instructed to 'let your mind wander' or 'think of nothing'. While these instructions appear appropriate to induce a 'resting‐state', they could induce distinct psychological and physiological states during the scan. In this study, we investigated whether different instructions affect mental state and functional connectivity (FC) (i.e. induce distinct 'resting states') during rs‐fMRI scanning. Thirty healthy subjects were subjected to two rs‐fMRI scans differing only in pre‐scan instructions: think of nothing (TN) and mind‐wandering (MW) conditions. Self‐reports confirmed that subjects spent the majority of the scanning time in the appropriate mental state. Independent component analysis extracted 19 independent components (ICs) of interest and functional network connectivity analyses indicated several conditional differences in FCs among those ICs, especially characterised by stronger FC in the MW condition than in the TN condition, between default mode network and salience/visual/frontal network. Complementary correlation analysis indicated that some of the network FCs were significantly correlated with their self‐reported data on how often they had the TN condition during the scans. The present results provide evidence that the pre‐scan instruction has a significant influence on resting‐state FC and its relationship with mental activities. Abstract : The differences in functional connectivity after two commonly used instructions for resting‐state fMRI studies ('think about nothing' and 'let your mind wander') were explored. Some increased connectivity in the 'let your mind wander' condition was found, in which the default mode network components showed greater connectivity with the occipital, temporal, and frontal networks. This study revealed that two common instructions had different effects on functional network connectivity.